PHP & MySQL everyday apps for dummies - Valade, Janet (--For dummies., 2005)
"PHP and MySQL Everyday Apps For Dummies is a one-stop reference providing all you need to build dynamic, real-world, ready-to-use apps with the popular PHP (a scripting language) and MySQL (a database system) software. Information on each application includes a discussion of issues, structure of the database, code listings, and an explanation of the code. You can use these applications as is, modify them for use on your Web site, or build your own application using techniques described. If you want real-world Web apps you can use right away, this is the book for you"--Resource description page